Food myths and facts - Woog, Adam (Nutrition & health, 2011)
From the Publisher: Lucent Books' Nutrition and Health series provides users with accessible information for evaluating the often conflicting and ever-changing issues surrounding nutrition and healthy living. Individual volumes focus on a specific health or nutrition-related topic, such as body image, diets and dieting, junk food, or vegetarianism. Each volume contains a topic overview, information about changing trends, up-to-date scientific analysis, and a look at controversies surrounding the featured subject. The narrative also contains personal anecdotes, informative sidebars, fact boxes, and statistics that help readers understand these topics and how they impact their bodies and their lives. Full-color photographs and detailed tables, charts, graphs and illustrations complement and enhance the text, while ancillary materials such as a glossary, a bibliography and a subject index provide useful tools for further research and discussion. The Nutrition and Health series is a valuable resource for anyone seeking clear, reliable, and timely information about today's biggest health and nutrition issues